Crowdfunding framework for waqf property optimisation of waqf institution / Nur Athirah Abd Rahman ... [et al.] - Abd Rahman, Nur Athirah; Abd Mutalib, Hasyeilla; Abdull Rahman, Nurul Labanihuda; Shafai, Nor Anis (2024)
Waqf property provides an institution with fortune and prosperity. Hence, waqf property must be utilised and managed properly to achieve the best results in eradicating poverty and improving people's well-being. During the 2023 Budget Presentation, Malaysian Prime Minister emphasised that only approximately 3,500 hectares, or merely 12 percent of the registered waqf land, has been successfully developed. This clearly shows that waqf institutions are dealing with problems in managing and optimising waqf property which affect the development and management of the property, which has an impact on the development and administration of the property. Furthermore, the organisation is unable to pool money efficiently due to a shortage of funds and the continued use of the traditional way of collecting waqf funds. Thus, there is a need to improve the management and the process of collecting funds for the purpose of optimising the waqf property. This study took on a qualitative method, employing a case study and purposive sampling to achieve the objective. Data were collected using formal, semi-structured in-depth interviews and document review. The significant findings of this study aim to propose the crowdfunding framework for the optimisation of waqf property by waqf institutions, which consists of four basic components; i) input; ii) process; iii) output; and iv) feedback. Through the development of this framework, waqf institutions will be able to increase the waqf funds using the crowdfunding platform. Furthermore, this framework will reduce the liquidity constraints among the waqf institutions and also create many spaces for collaboration between waqf institutions and other agencies. Additionally, by optimising more waqf property in Malaysia, this approach will boost public confidence and trust in waqf organisations. This framework is adaptable to various types of waqf institutions in order to promote more proactive and optimum growth and optimisation of waqf property.